Manajemen Bandwidth Pelanggan Pada Jaringan PS Core Menggunakan Service Aware Policy Control Sebagai PCRF - Elza Chaerunnisa; Irmayani Irmayani (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
Abstract In this essay discussed users bandwidth management at PS Core Networks. The PCRF (Policy Charging rule function) that created the SAPC (Service Aware Policy Control) serves as policy makers on the PS core network in the regulation of Quality of Service (QoS) which is obtained by the customer. Package made ​​in the implementation of a one -week unlimited package with first Bandwidth MBR is 3.6 Mbps downlink for 3G, 2 Mbps donlink for 2G, and 512 Kbps uplink for both. With FUP (Fair Usage Policy) on quota of 125 Mbyte and 250 Mbyte. At the FUP point change customer bandwidth QoS values ​​modified by the rules that have been made ​​in the SAPC, decreasing bandwidth to be 512 Kbps downlink and uplink, and after second FUP the bandwidth MBR to be 64 Kbps for downlink and 512 Kbps for uplink. Gx SR performance above 99%, declare that stating connection and transaction between GGSN and SAPC processing well. Success rate PDP context activation for apn xlunlimited in GGSN give information that sum of active subscriber for broadband unlimited in a one -week close the average 858.272 subscriber per day. Use of this PCRF be beneficial symbiosis between internet service providers and customers. Customers with low prices can use the internet access for one week, and Internet service providers received an increasing number of customers. Keywords: SAPC, PCRF, PS Core, Quality of Service.